Strategi Pendidikan Islam Dalam Membangun Karakter Multikultural Pada Peserta Didik - Muhammad Najmi Hayat; Rifaldi Jaziadi Rossi; Maula Qorry Ainayya; Mu’alimin Mu’alimin (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Islamic education has a strategic role in shaping the character of students who are able to live harmoniously in a multicultural society. Islamic values ​​such as tolerance, mutual respect and cooperation must be taught to promote harmony amidst cultural, ethnic and religious differences. Although Islamic teachings support inclusivity and respect for diversity, its practice is often faced with challenges. Therefore, an Islamic education approach with a multicultural perspective is needed to teach students to understand that differences are God's decree and must be seen as a social force. This educational concept needs to prioritize human values, moderation and openness, as well as integrating diversity in learning. Through education that emphasizes multiculturalism, it is hoped that a generation that not only adheres to religion but is also able to maintain social harmony can be formed. This research also identifies challenges in implementing multicultural education in Islamic schools and offers strategies to overcome these obstacles.